KECANTIKAN WANITA DALAM TEKS RUKMINI TATTWA - Ni Made Yunitha Asri Diantary (Jnanasidanta, 2019)
Beauty is synonymous with a woman, beauty is categorized as physical beauty and spiritual beauty. Women are directed to have both types of beauty, physical beauty can be obtained from body care and spiritual beauty obtained by practicing religious teachings such as Tri Kaya Parisudha and Dasa Niyama Brata. Care for the physical body can be done with the principle of dharma by giving priority to the quality of food, cleanliness of the body and doing yoga. The text of Rukmini Tattwa also provides a way to naturally care for the beauty of a woman's body. This text prioritizes how a woman can become a virgin again. This is important for building harmonious relationships within the family. A well-maintained body will raise gods in a woman's bodykey words: Women's Beauty, Text of Rukmini Tattwa